Faktor – Faktor yang Mempengaruhi Penyaluran Kredit pada Bank Umum di Indonesia - Gayo, Absyirni Ari; Prihatni, Rida; Armeliza, Diah (Jurnal Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of Third Party Funds, Non-Performing Loans, Capital Adequacy Ratio, BOPO and Net Interest Margin on Credit Distribution. The independent variables used in this research are Third Party Funds, Non-Performing Loans, Capital Adequacy Ratio, BOPO and Net Interest Margin. The dependent variable used in this study is Credit Distribution. This study uses secondary data, namely the annual reports of companies listed on the Indonesia Stock Exchange for the 2017-2020 period (168 observations). The sampling method used in this research is the purposive sampling method. This study uses a panel data analysis method which is processed using the E-Views 12 application. The results show that Third Party Funds have a positive effect on Credit Distribution. Non-Performing Loans have no effect on Credit Distribution. Capital Adequacy Ratio has no effect on Credit Distribution. BOPO has no effect on Credit Distribution. Net Interest Margin has a positive effect on Credit Distribution.